Bibliometric analysis on the literature of monk fruit extract and mogrosides as sweeteners - Yeung, Andy Wai Kan (Frontiers in Nutrition, 2023)
The evolution of research literature on monk fruit extract and mogroside as sweeteners has yet to be investigated. No study has evaluated this literature from a bibliometric perspective. This bibliometric study analyzed the relevant research literature indexed in Web of Science, to unveil its growth and the most productive authors, institutions, countries, journals, and journal categories. In addition, this study aimed to identify the recurring themes of the literature. On July 2023, the Web of Science Core Collection database was accessed with the following search query: TS=(*mogroside* OR “luo han guo” OR “lo han kuo” OR “monk fruit*” OR “monkfruit*” OR “Siraitia grosvenorii”) AND TS=(sweet*). The search identified publications mentioning these terms in their title, abstract, or keywords. Only articles and reviews were included. No additional filters were placed on publication year, language, etc. Basic publication and citation frequency counts were recorded directly from the database. The complete record of the publications were exported into VOSviewer and CRExplorer, for visualization of recurring terms and identification of commonly cited references, respectively. The search yielded 155 publications. Publication and citation counts have increased steadily since the 2010s. The most productive authors and institutions were mostly based in Asian countries, such as China, Japan, and Singapore. Nearly half of the publications had contributions from China and were published in journals concerning food science technology. The health effects and biosynthesis of mogrosides were the recurring themes among the top 10 most cited publications. Most of the health effects, such as anti-hyperglycemic, anti-hyperlipidemic, and anti-diabetic properties, were demonstrated in animal models with limited evidence from clinical trials. Future studies should focus on testing in humans. Since monk fruit extracts were generally recognized as safe (GRAS) according to the Food and Drug Administration (FDA), the affirmation of these health benefits in humans by future studies should advocate its use in the food industry and the society to generally improve the public health.